1981
DOI: 10.1063/1.441014
|View full text |Cite
|
Sign up to set email alerts
|

Reactive cross section as a function of reagent energy. II. H(D)+HBr(DBr)→H2(HD,D2)+Br

Abstract: A crossed molecular beam study has been made of reactive cross section as a function of collision energy Sr(ET) for all isotopic variants of the abstraction reaction H′+H″Br→H′H″+Br. The apparatus incorporates, for reagent preparation, a supersonic source of variable-energy H or D atoms, and, for product detection, a tunable vacuum ultraviolet laser to obtain laser-induced fluorescence of Br. The cross-section functions indicate that the threshold energy for reaction is <1 kcal/mol. At enhanced collisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…As we have already stated, the smaller the value of the parameter p, the greater the reaction cross section should be. Table I presents [7]. Our computations show that these conclusions are also valid for vibrationally excited states of the reactants.…”
Section: Mass Effects On the Reaction Cross Sectionsupporting
confidence: 68%
See 1 more Smart Citation
“…As we have already stated, the smaller the value of the parameter p, the greater the reaction cross section should be. Table I presents [7]. Our computations show that these conclusions are also valid for vibrationally excited states of the reactants.…”
Section: Mass Effects On the Reaction Cross Sectionsupporting
confidence: 68%
“…The LEPS surface used was taken from Sudhakaran and Raff's paper [6] denoted there as surface 111. The authors determined it so as to reach a value of the height of the barrier for reaction (4a) close to the experimental value that they abstracted from other studies [7,8]. For each of the four values of the collision energy (E = 8.4, 20.9, 29.3, and 41.8 kJ/mol), we calculated 600 trajectories with b,,, = 3 X lo-'' m, J (for HBr) = 4 and J (for DBr) = 16.…”
Section: Resultsmentioning
confidence: 85%
“…In the case of HDCO, rotational assignments were not available and the laser was operated without an etalon (0.4 cm-I bandwidth) and grating tuned to maximize the CO signal. In all experiments reported here the UV beam (15 ns pulse duration) was expanded using a telescope consisting of two quartz cylindrical lenses to give a beam size of ,..., 15 by 4 mm at the entrance to the photolysis cell, with pulse The vacuum ultraviolet probe laser system was patterned after the Toronto system described by Hepburn et al 29 Frequency-tripled radiation from a Nd: Y AG laser (Quanta-Ray OCR-lA) was used to pump two dye lasers. One of these dye lasers (Lambda-Physik model 2002) was fixed at a wavelength of -430.9 nm (Stilbene 420), corresponding to a two-photon resonance in magnesium (WI).…”
Section: Methodsmentioning
confidence: 99%
“…It is conjectured that in the former reaction, the repulsive energy R with initial rovibrational excitation is comparatively greater, which would cause more sensitivity of the product polarizations to the initial vibrational and rotational excitations in the N( 4 S) + H 2 reaction. The two reactions belong to the reaction type of the heavylight-light (HLL) mass combination, and according to the pioneering studies 44,45 of Polanyi and coworkers focusing on the reactions of D+HBr and H+DBr with the same type of mass combination, the mass of the attacking atoms and the moment of inertia of the diatom should have influence on alignment effect. They found that alignment effect increases in the reaction with heavy attacking atoms, and low moment of inertia of the diatom.…”
Section: Discussionmentioning
confidence: 99%